Electromagnetic shoot - Sousa, João (2008)
The science fair device described in this paper shoots a miniature soccer ball using a solenoid and a two-piece rod made of iron and nylon. The nylon part of the rod is introduced inside the solenoid and a ball is placed at its extremity. When an electrical current passes through the solenoid, the iron part of the rod is pushed into its center, causing the shooting of the ball. This mechanism, originally developed for Minho Team soccer robots, has been successfully used for several years. The science fair version includes a slewing iron case and overheat protections.